Vlog: A New Communication Practice in Post Pandemic - Hong Lin Liu (Universitas Muhammdiyah Yogyakarta, 2021)
The COVID-19 epidemic has triggered a large-scale global transmission event, and Vlog has emerged from many transmission media. It quickly adapts to the new trend of online social media during the epidemic, and represents the new trend of video-based social media. Based on the theoretical basis of user production, this article sorts out the development history of Vlog, lists typical cases of vlog during the epidemic, analyzes the new thinking of social interaction brought about by the spread of vlog, and analyzes the new communication practice in post pandemic.